Holistic assessment of the environmental trade-offs of novel aircraft - Stevens, Joy; Maldonado, Ana Luisa; Proenca, Anderson R. (American Institute of Aeronautics and Astronautics (AIAA), 2026)
This paper presents a high-level, scenario-based methodology for the integrated assessment of aircraft noise, CO2, NOx and PMtotal emissions at an airport fleet level during standardised ICAO landing-and-take-off (LTO) operations. The approach extends a regression-based noise contour area model derived from ICAO certification data and calibrated against higher-fidelity modelling, and combines this with standard industry methods for CO2 and air pollutant emissions to enable rapid comparison across different airport fleet mixes, incorporating different aircraft generations and novel propulsion technologies. The methodology is applied to a UK airport case study to explore future fleet evolution pathways including technology progression and fleet renewal rates. The results show that the uptake of next-generation conventional aircraft reduces fleet-level noise, CO2 and PMtotal but increase NOx emissions, whilst hydrogen and electric aircraft reduce fleet-level CO2, NOx and PMtotal emissions but increase noise contour areas. These findings demonstrate that future fleet transitions may deliver uneven environmental improvements, highlighting the necessity of an integrated noise and emissions evaluation framework to support aircraft design decisions, airport planning, and policy development.